Team ball sport experience minimizes sex difference in visual attention - Jin, Peng; Ge, Zhigang; Fan, Tieming (Frontiers in Psychology, 2022)
Simultaneous tracking of the position of the ball and player locations and activities places high demands on visual attention in team ball sport athletes. Owing to their extensive sports training, these athletes may be expected to exhibit visual attention skills superior to non-athletes; however, the results of studies examining this are inconsistent. Thus, the first aim of this study was to assess the impact of participating in a team ball sport on visual attention. There is limited empirical evidence indicating a sex difference in visual attention, and few studies have reported on visual attention in male and female athletes. Thus, the second aim of this study was to determine whether team ball sport experience affected any sex differences in visual attention. In total, 44 highly skilled basketball players—22 men (mean age: 21.86 ± 2.15 years) with a mean (SD) of 8.46 (2.92) years training experience and 22 women (mean age: 21.32 ± 1.58 years) with a mean (SD) of 8.22 (2.44) years of training experience—and 44 non-athletic undergraduate college students—22 men (mean age: 21.62 ± 1.88 years) and 22 women (mean age: 21.55 ± 1.72 years)—were recruited and completed this study. Visual attention was measured by using the multiple object tracking (MOT) task. Skilled basketball players showed superior tracking accuracy to non-athletic college students on the MOT task. A significant sex difference was found only among the non-athletic college students, with better tracking accuracy for men than for women on the MOT task. By contrast, no significant sex difference was observed among the skilled basketball players for tracking accuracy on the MOT task. These findings indicated that team ball sport training may enhance visual attention as assessed by tracking accuracy. Given that the male and female basketball players in this study had similar training experience and game performance demands, long-term team ball sport experience appeared to minimize the sex difference in visual attention found among non-athletic students.